Challenges of diagnostic exome sequencing in an inbred founder population. Issue 2 (22nd April 2013) - Azmanov, Dimitar N.; Chamova, Teodora; Tankard, Rick; Gelev, Vladimir; Bynevelt, Michael; Florez, Laura; Tzoneva, Dochka; Zlatareva, Dora; Guergueltcheva, Velina; Bahlo, Melanie; Tournev, Ivailo; Kalaydjieva, Luba
Abstract Exome sequencing was used as a diagnostic tool in a Roma/Gypsy family with three subjects (one deceased) affected by lissencephaly with cerebellar hypoplasia (LCH), a clinically and genetically heterogeneous diagnostic category. Data analysis identified high levels of unreported inbreeding, with multiple rare/novel "deleterious" variants occurring in the homozygous state in the affected individuals. Step‐wise filtering was facilitated by the inclusion of parental samples in the analysis and the availability of ethnically matched control exome data. We identified a novel mutation, p.Asp487Tyr, in the VLDLR gene involved in the Reelin developmental pathway and associated with a rare form of LCH, the Dysequilibrium Syndrome. p.Asp487Tyr is the third reported missense mutation in this gene and the first example of a change affecting directly the functionally crucial β‐propeller domain. An unexpected additional finding was a second unique mutation (p.Asn494His) with high scores of predicted pathogenicity in KCNV2, a gene implicated in a rare eye disorder, retinal cone dystrophy type 3B. This result raised diagnostic and counseling challenges that could be resolved through mutation screening of a large panel of healthy population controls. The strategy and findings of this study may inform the search for new disease mutations in the largest European genetic isolate.